Contributions of Algerian Students to the National Movement and the Algerian liberation révolution - gherin, abdenour; kellil, malika (The Algerian Historical Journal, 2026)
Since the beginning of the twentieth century, Algerian students have realized the heavy burdens they will have to bear in the cause of their country, confident in the results of the struggle for liberation and independence. They must prepare themselves to face the new responsibilities entrusted to them to publicize the grievances of French colonialism in the universal and French universities and to emphasize the existence of an Algerian nation and people who have not and will not be fused with France. Believing in this new task, these students did not hesitate to sacrifice for the Algerian Revolution. This study aims to re-read aspects of the struggle of Algerian students based on new documents to understand how to mobilize the student movement abroad around the goals of the Algerian revolution.